2022
DOI: 10.1097/shk.0000000000002036
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Induces Intravascular Hemolysis, Exacerbated by Red Blood Cell Transfusion and Associated With Disrupted Arginine–nitric Oxide Metabolism

Abstract: Background: Severe injury can provoke systemic processes that lead to organ dysfunction, and hemolysis of both native and transfused red blood cells (RBCs) may contribute. Hemolysis can release erythrocyte proteins, such as hemoglobin and arginase-1, the latter with the potential to disrupt arginine metabolism and limit physiologic NO production. We aimed to quantify hemolysis and arginine metabolism in trauma patients and measure association with injury severity, transfusions, and outcomes. Methods: Blood was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In addition to increased lipolysis metabolites, our data revealed decreases in citrulline, arginine, and proline metabolites, which has been described in previous TBI metabolomic investigations 44 . These same changes have been observed in critically injured patients and those in hemorrhagic shock 37 and linked to adverse clinical outcomes 45 . These reductions in arginine ultimately lead to reduction in nitric oxide necessary to maintain cerebral perfusion.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to increased lipolysis metabolites, our data revealed decreases in citrulline, arginine, and proline metabolites, which has been described in previous TBI metabolomic investigations 44 . These same changes have been observed in critically injured patients and those in hemorrhagic shock 37 and linked to adverse clinical outcomes 45 . These reductions in arginine ultimately lead to reduction in nitric oxide necessary to maintain cerebral perfusion.…”
Section: Discussionsupporting
confidence: 84%
“…44 These same changes have been observed in critically injured patients and those in hemorrhagic shock 37 and linked to adverse clinical outcomes. 45 These reductions in arginine ultimately lead to reduction in nitric oxide necessary to maintain cerebral perfusion. Further, ornithine, a crucial part of the arginine and nitric oxide pathway, was significantly decreased in TBI patients after dura violation, as seen in previous TBI literature.…”
Section: Discussionmentioning
confidence: 99%
“…We know from clinical studies that major trauma is associated with endogenous hemolysis and that markers of hemolysis before transfusion correlate with physiologic markers of injury severity, and poor outcomes (6,8). Clinical studies also demonstrated that large-volume transfusion (> 5 L) is associated with a BUN = blood urea nitrogen, Cr = creatinine, NGAL = neutrophil gelatinase-associated lipocalin, NO = nitric oxide, SCD = sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…43 Implementation of omics technologies in the field of coagulopathy of trauma has generated a wealth of data corroborating well-established literature on coagulation and fibrinolytic cascades as a balancing act between proteases and protease-inhibitor systems, 5 and providing for the first time structural molecular evidence of fibrinolytic products beyond clinically accepted markers of fibrin breakdown such as d-dimers. 26 However, despite extensive omics characterization of PLT products 32,[44][45][46][47][48] as they are stored in the blood bank, as well as the signatures associated with the onset and severity of trauma-associated thrombo-inflammatory comorbidities, 4,13,15,16,24,25,46,[49][50][51][52][53] no study to date has focused on the molecular impact of PLT transfusion on the circulating proteome and metabolome of severely injured patients.…”
Section: Discussionmentioning
confidence: 99%